IMPLEMENTASI KEBIJAKAN PENGEMBANGAN INDUSTRI TENUN SONGKET - Agus Setiawati; Tuti Khairani Harahap; Meyzi Heriyanto (Universitas Riau, 2017)
Implementation of Songket Songket Development Policy. The purpose of this research is to know the implementation in policy of songket weaving industry development in Pekanbaru city. This research is a qualitative research. The research informants were Head of Department of Trade and Industry, community shop, songket weaving artist and academician. Data collection techniques are interviews, observation and documentation. Data analysis through triangulation process. The result of the study shows that the implementation of policy of songket weaving industry development in Pekanbaru city has not been implemented optimally. The factors found are policy access, human resources, market access, lack of promotion from the government, and low innovation and competitiveness.